A mutation protective against Alzheimer's disease renders amyloid β precursor protein incapable of mediating neurotoxicity. (10th April 2014) - Hashimoto, Yuichi; Matsuoka, Masaaki
Abstract Expression of a familial Alzheimer's disease (AD)‐linked mutant of amyloid β precursor protein (APP) or the binding of transforming growth factor β2 to wild‐type (wt)‐APP causes neuronal death by activating an intracellular death signal (a APP‐mediated intracellular death signal) in the absence of the involvement of amyloid β (Aβ) toxicity in vitro. These neuronal death models may therefore be regarded as Aβ‐independent neuronal death models related to AD. A recent study has shown that the A673T mutation in the APP isoform APP770, corresponding to the A598T mutation in the most prevalent neuronal APP isoform APP695 (an AD‐protective mutant of APP), is linked to a reduction in the incidence rate of AD. Consistent with this, cells expressing the AD‐protective mutant of APP produce less Aβ than cells expressing wt‐APP. In this study, transforming growth factor β2 caused death in cultured neuronal cells expressing wt‐APP, but not in those expressing the AD‐protective mutant of APP. This result suggests that the AD‐protective mutation of APP reduces the incidence rate of AD by attenuating the APP‐mediated intracellular death signal. In addition, a mutation that causes hereditary cerebral hemorrhage with amyloidosis‐Dutch type also attenuated the APP‐mediated intracellular death signal. <boxed-text content-type="graphic" id="jnc12717-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text> The A598T mutation of amyloid precursor protein APP is linked to a reduction in the incidence rate of Alzheimer's disease (AD). This study shows that TGFβ2 causes death in neuronal cells expressing wild‐type APP, but not in those expressing the AD‐protective mutant of APP, suggesting that the AD‐protective mutation of APP reduces the incidence rate of AD by attenuating the APP‐mediated intracellular death signal.